Global crisis of the ?innovation for development?. From positivism to constructivism for creating locally sustainable lifestyles - de Sousa Silva, Jose (Cuban Journal of Agricultural Science, 2014)
The ?development? is in crisis (Domenach 1980); our way of innovating requires to be innovated. Ruptures and paradigmatic emergencies are the epicenters of the civilizatory changes transforming the human and nonhuman lifestyles since the second half of the XX century. With difference speeds and degrees of intensity, all the spheres of existence, fields of knowledge and human processes experience changes derived from the global crisis. The study identifies paradigmatic transformations for innovation organizations related with the field of local development. The classical innovation paradigm of modern science, in which some create, other transfer and the rest adopt, under its universal, mechanic, neutral and positivist rationality, lost its monopoly for the contextual, interactive and ethical-constructivist paradigm in studies of phenomena whose nature and dynamics depend on human perception.